Efek Penambahan Sari Buah Mengkudu (Morinda citrifolia L.) pada Roti Tawar terhadap Kadar Glukosa Darah Pada Tikus yang Diinduksi Aloksan - Nurul Laelatunisa; Nikmatul Rizky; Rachmadanti Arum; Rista Anggriani (Food Technology and Halal Science Journal, 2019)
Noni (Morinda citrifolia L) has been known to have antihyperglycemic activity. Xeronine compounds, alkaloids, which play a role in controlling blood glucose. In the previous research, researchers have made white bread with the addition of noni juice, but there has not been an analysis of its antihyperglycemic activity. So this study aims to determine the effect of white bread with the addition of noni juice (50, 150, 250ml) on the reduction of blood glucose in vivo. Male white mouse mice aged 3 months were grouped into 7 groups namely negative control, positive control, noni juice, noni juice without bread, and noni juice with noni juice (50,100, and 150 mL). All groups except the negative controls were induced with 200 mL alloxan until the rats were declared hyperglycemic (blood glucose> 135 mg / dL). After that the rats have fasted, then blood glucose levels before and after being given bread were measured every 30 minutes until the 120th minute. Blood glucose measurements are measured directly through the tail vein using a glucometer. In addition, white bread is also tested qualitatively alkaloids. The results obtained with the addition of 250 ml noni juice can reduce 33 mg / dL after consumption. White bread with the addition of noni juice shows positive alkaloid content.